2008
DOI: 10.1111/j.1600-0870.2007.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Using flow geometry for drifter deployment in Lagrangian data assimilation

Abstract: Methods of Lagrangian data assimilation (LaDA) require carefully chosen sites for optimal drifter deployments. In this work, we investigate a directed drifter deployment strategy with a recently developed LaDA method employing an augmented state vector formulation for an Ensemble Kalman filter. We test our directed drifter deployment strategy by targeting Lagrangian coherent flow structures of an unsteady double gyre flow to analyse how different release sites influence the performance of the method. We consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…This means that rather than solving Equation (11) directly, each point of our ensemble is evolved using the dynamical model given by Equation (1). Salman et al (2006Salman et al ( , 2008 extended the approach of Evensen (1994) by approximating the PDF φ(x, t) of the augmented state vector using an analogous expression to Equation (13). This follows from the fact that both Equations (5) and (11) have identical forms.…”
Section: A Grid/particle Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that rather than solving Equation (11) directly, each point of our ensemble is evolved using the dynamical model given by Equation (1). Salman et al (2006Salman et al ( , 2008 extended the approach of Evensen (1994) by approximating the PDF φ(x, t) of the augmented state vector using an analogous expression to Equation (13). This follows from the fact that both Equations (5) and (11) have identical forms.…”
Section: A Grid/particle Methodsmentioning
confidence: 99%
“…The highly nonlinear nature of Lagrangian trajectories is our primary motivation for developing a new method that directly targets these highly nonlinear attributes of Lagrangian data. A second motivation is driven by recent efforts to develop an optimum drifter deployment strategy by analyzing the underlying flow geometry (Molcard et al, 2006;Salman et al, 2008). These studies have revealed that optimum drifter deployment sites can be realized by targeting hyperbolic trajectories of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…These methods detect LCSs, which form finite-time boundaries and govern the mixing and transport of tracers (Shadden et al, 2005;Haller and Yuan, 2000; and have proven useful in a variety of geophysical flows, see e.g. Salman et al (2008);Tang et al (2009);Koh and Legras (2002); Joseph and Legras (2002); Cohen and Schultz (2005).…”
Section: Flow Boundariesmentioning
confidence: 99%
“…The resulting observation operator in this methodology is then the identity in the instrument coordinate at observation instances, for example, times at which the instrument has surfaced and where it can report its location. Several theoretical and applied studies have successfully assimilated Lagrangian data in the context of ocean modelling (Salman et al, 2006;Taillandier et al, 2006Taillandier et al, , 2008Restrepo, 2008;Salman et al, 2008;Mariano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%